Role of Human Epicardial Adipose Tissue-Derived miR-92a-3p in Myocardial Redox State - Carena, Maria Cristina; Badi, Ileana; Polkinghorne, Murray; Akoumianakis, Ioannis; Psarros, Costas; Wahome, Elizabeth; Kotanidis, Christos P; Akawi, Nadia; Antonopoulos, Alexios S; Chauhan, Jagat; Sayeed, Rana; Krasopoulos, George; et al. (Journal of the American College of Cardiology, 2023)
Visceral obesity is directly linked to increased cardiovascular risk, including heart failure. This study explored the ability of human epicardial adipose tissue (EAT)-derived microRNAs (miRNAs) to regulate the myocardial redox state and clinical outcomes. This study screened for miRNAs expressed and released from human EAT and tested for correlations with the redox state in the adjacent myocardium in paired EAT/atrial biopsy specimens from patients undergoing cardiac surgery. Three miRNAs were then tested for causality in an in vitro model of cardiomyocytes. At a clinical level, causality/directionality were tested using genome-wide association screening, and the underlying mechanisms were explored using human biopsy specimens, as well as overexpression of the candidate miRNAs and their targets in vitro and in vivo using a transgenic mouse model. The final prognostic value of the discovered targets was tested in patients undergoing cardiac surgery, followed up for a median of 8 years. EAT miR-92a-3p was related to lower oxidative stress in human myocardium, a finding confirmed by using genetic regulators of miR-92a-3p in the human heart and EAT. miR-92a-3p reduced nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase-derived superoxide (O ) by targeting myocardial expression of WNT5A, which regulated Rac1-dependent activation of NADPH oxidases. Finally, high miR-92a-3p levels in EAT were independently related with lower risk of adverse cardiovascular events. EAT-derived miRNAs exert paracrine effects on the human heart. Indeed miR-92a-3p suppresses the wingless-type MMTV integration site family, member 5a/Rac1/NADPH oxidase axis and improves the myocardial redox state. EAT-derived miR-92a-3p is related to improved clinical outcomes and is a rational therapeutic target for the prevention and treatment of obesity-related heart disease.